Complementary and alternative medicine use among elderly patients living with chronic diseases in a teaching hospital in Ethiopia. (December 2017) - Ayele, Asnakew Achaw; Tegegn, Henok Getachew; Haile, Kaleab Taye; Belachew, Sewunet Admasu; Mersha, Amanual Getnet; Erku, Daniel Asfaw
Highlights: The use of complementary and alternative medicine (CAM) among patients with chronic diseases has grown rapidly worldwide. Institution-based cross-sectional survey was conducted among elderly patients with chronic disease attending outpatient clinic. Herbal medicine and spiritual healing being the most commonly utilized CAM modalities (50.4% and 40.8% respectively). This survey revealed a higher rate of CAM use among elderly patients with chronic diseases. Special attention should be given for these patient population due to the potentially harmful interaction of herbal remedies with medications. Abstract: Background: The use of complementary and alternative medicine (CAM) among patients with chronic diseases has grown rapidly worldwide. Yet, little has been known about CAM use by elderly patients with chronic diseases in Ethiopia. This study aimed at assessing the prevalence and reasons for CAM utilization among elderly patients living with chronic diseases in Ethiopia. Methods: An institution-based quantitative cross-sectional survey was conducted among elderly patients with chronic disease attending outpatient ambulatory clinics of University of Gondar referral and teaching hospital (UoGRTH). An interviewer-administered and semi-structured questionnaire were utilized to collect the data. Result: Of the total respondents, 240 (74%) reported the use of CAM, with herbal medicine and spiritual healing being the most commonly utilized CAM modalities (50.4% and 40.8% respectively). Dissatisfaction with conventional therapy (40.8%) and belief in the effectiveness of CAM (30.8%) are the most commonly cited reasons for the use of CAM therapies. Rural residency, higher educational status, higher average monthly income and presence of co-morbidity were positively associated with the use of CAM. Conclusion: This survey revealed a higher rate of CAM use among elderly patients with chronic diseases, along with a very low rate of disclosing their use to their health care providers. Special attention should be given for these patient population due to the potentially harmful interaction of different herbal remedies with the prescribed medications, thereby predisposing the patient to untoward adverse effects and compromised overall health outcome.